ANALISIS SWOT 8-K PADA OBJEK WISATA REKREASI DAN HIBURAN KELUARGA KID’S FUN YOGYAKARTA - Sulistyo, Agung (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2017)
A good company should be able to know what the desire of customers, provide good service, and do some innovations in running the business. An Implementation of good strategy will make the company to survive in a long time. This study was conducted to look at the strategies that must be done by Kid's Fun as the provider for entertainment and recreation for family by using SWOT 8-K analysis. Based on the last research, it can be concluded that Kid's Fun is in quadrant I-B, and then they can do the Stable Growth Strategy. There's an opportunity to be better, which is located in I-A quadrant. The management can enhance existing strengths and minimize the weaknesses. This is in line with existing market potential, supports from local government, economic conditions and technological developments that supporting the companies. Keywords: Competitive Strategy, SWOT 8-K Analysis Kids Fun Yogyakarta